An unusual pattern of endometrial involvement: superficial spreading squamous cell carcinoma of the cervix - Jiang, Xiaolin; Han, Zhirong; Chun, Zhiping; Wen, Bingyang; Chen, Tingan (Frontiers in Oncology, 2024)
BackgroundCervical squamous cell carcinoma (SCC) is the most common type of cervical carcinoma. Usually, the cancer metastasizes through lymphatic or hematogenous dissemination. However, it is uncommon for a superficial spreading of cervical cancer to reach the endometrium, fallopian tubes, and the ovaries.ObjectivesIn the present study, we report 15 cases of superficial spreading SCC and discuss the possible mechanism involved.MethodsWe collected 15 samples diagnosed by histopathology after surgery. Immunostaining, which included P16, P63, CD138, CD34, D2-40, and Ki-67, were performed for all samples.ResultsAll patients were postmenopausal or perimenopausal women. The commonest clinical presentation was vaginal bleeding in 66.67%. All patients were infected with HPV 16. The endometrium was replaced by high-grade squamous intraepithelial lesion (HSIL), which involved the endometrial gland, even squeezing into the myometrium and forming SCC. Bilateral fallopian tubes and ovaries involvement was in 1/15. A total of 10/15 (66.67%) of the women had disease of stage 1B or less. All SCCs were moderately or poorly differentiated. Immunohistochemistry revealed that the tumor cells were positive for P63 and P16, with a high Ki-67 labeling index. There was CD138 positive expression in varying degrees, which was strongly and diffusely expressed in 6/15 (40.00%).ConclusionSuperficial spread of cervical cancer towards the endometrium is a rare but cognizable phenomenon, and a guideline for the management of these cases has not been established. Our present findings suggest that multiple factors may interact with each other simultaneously, contributing to this rare disease.